Improvements in depression symptomatology in a sample of undergraduate students: a pre-post Balint group intervention study - Shuzhi Zhou; Keyi Qin; Qian Gu; Rui Zhang; Lixia Wang; Jinjing Luo; Jincong Yu; Chuanhua Gu (BMC Psychology)
Abstract Background/Objective Previous studies have explored the effects of Balint group interventions on reducing depressive symptoms among medical workers; however, its effects on other populations have not been analyzed. This study addressed this gap by investigating whether this intervention can reduce depressive tendencies in college students and its potential mechanism. Methods The effects of the 6-week Balint group intervention were assessed using an experimental/control group and pre-/post-test design. 56 college students (66.07% female; baseline Mage = 21.56 years, SD = 1.86) participated in the study, and 30 students (baseline Mage = 21.84 years, SD = 2.02) were included in the intervention group. Results Consistent with developmental expectations, the results indicated that after 6 weeks, the intervention group exhibited significantly lower depressive tendencies and significantly improved perceived social support and interpersonal competences compared to the waiting control group. Furthermore, interpersonal competence, particularly disclosure, fully mediated the relationship between the Balint group intervention and depressive tendencies. Conclusions Balint group intervention can significantly reduce depressive tendencies and improve perceived social support and interpersonal competences of college students. The decrease of depressive tendencies can be achieved by improving college students’ interpersonal competences (especially disclosure). Clinical trial number The clinical trial was registered in the Chinese Clinical Trial Registry (Registration number: ChiCTR2400090160) on 25 September 2024.